Kondisi habitat mangrove di Kelurahan Mapane Kecamatan Poso Pesisir Kabupaten Poso - Reski, Nurain; Toknok, Bau; Korja, I Nengah; Yani, Rendy Ahmad (ULIN: Jurnal Hutan Tropis, 2024)
The aim of this study is to assess the mangrove habitat condition in Mapane Village, Poso Coastal District, Poso Regency. Field surveys were conducted to determine representative mangrove habitat conditions (physical and chemical) in Mapane Village. Soil and water samples were collected to assess mangrove habitat conditions, using purposive sampling method with 3 repetitions. The soil and water quality in the research area is still conducive for mangrove growth, with suitable soil texture for Rhizophora sp. and stable salinity at 34‰. Although soil pH is slightly below standard, it remains suitable for mangrove growth (pH 6-7). Water quality parameters approach quality standards, albeit some below, remaining productive according to previous studies. The optimal pH for mangrove growth is neutral (pH 6.6-7.5). In conclusion, the soil and water quality in the research area strongly support mangrove growth. Despite slightly below-standard soil pH, it remains suitable for mangrove growth. Previous studies indicate the optimal soil pH for mangroves ranges from 6-7, while water pH approaches quality standards, remaining productive despite some below, and below pH levels.